2005
DOI: 10.1002/ppul.20230
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic findings in children with obstructive sleep apnea: Effects of age and hypotonia

Abstract: Obstructive sleep apnea (OSA) syndrome is a common disorder among children and is often associated with significant morbidity. The causes of OSA are related to either fixed upper airway abnormalities such as adenotonsillar hypertrophy, or dynamic airway abnormalities such as laryngomalacia and pharyngeal wall collapse. The aim of the present study was to determine the prevalence of dynamic upper airway abnormalities, based on endoscopic findings, in normotonic and hypotonic children with polysomnographically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 21 publications
3
38
0
Order By: Relevance
“…In children, enlargement of adenoid or tonsils, in association with increased upper airway collapsibility, is by far the most common cause of OSAS (18). In addition, obesity may cause obstructive sleep-related breathing disorders, as has also been found in adults (19).…”
Section: Discussionmentioning
confidence: 99%
“…In children, enlargement of adenoid or tonsils, in association with increased upper airway collapsibility, is by far the most common cause of OSAS (18). In addition, obesity may cause obstructive sleep-related breathing disorders, as has also been found in adults (19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 88.2% of these infants presented without stridor. 17 The authors argued that the high Includes nervous system conditions and anomalies and cerebral palsy. b Includes peri-, endo-, and myocarditis and cardiomyopathy; hypertension; acute myocardial infarction; coronary artery disease/other heart diseases; pulmonary heart disease; conduction disease and dysrhythmia; and congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…A 2005 study of children with obstructive sleep apnea demonstrated that dynamic airway collapse in infants without neurologic deficits decreased progressively as those children aged. 1 However, dynamic airway obstruction in hypotonic children did not improve with time. By the age of 2 years, 83% of hypotonic children demonstrated a dynamic obstruction compared with only 17% of normotonic patients.…”
mentioning
confidence: 98%